PERKEMBANGAN ASAS PARTISIPASI DALAM PERATURAN USAHA PENYEDIAAN SARANA WISATA TIRTA - Wira Yudha, Galang; Wairocana, I Gusti Ngurah; Dyah Satyawati, Ni Gusti Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 07, November 2013, 2013)
Bali’s island has a natural beauty and a very distinctive culture that makes Bali’s becoming the prime tourism destination, one of those is water tourism. As one of tourist destination, the tourism sector management involves not only the government but also the optimal role of the private sector and community participation is also needed. This study aims to look at how the implementation of the principle of participation in the Law of Tourism and its implementing regulations. Research methods is used for this type of normative research. The principle of participation in regulations No 10 of 2009 explained that everyone is entitled to participate in the process of tourism development. Then Bali Provincial Government of Bali Province also issued Regulations No 7 of 2007 concerning Usaha Penyediaan Sarana Wisata Tirta. Application of the principle of participation in the implementation of the regulations states that the public which is given the opportunity to participate in the decision-making process in the business of supplying water tourism facilities. In this case, two products are experiencing a mismatch between the legal basic of the regulation implement
Keywords: Provision of Tourism, Water Tourism, Participation